1982
DOI: 10.1161/01.cir.66.6.1154
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial function in areas of heterogeneous perfusion after coronary artery occlusion in conscious dogs.

Abstract: SUMMARY Regional myocardial function and blood flow in endocardial layers were correlated in myocardial segments subtending severely ischemic and adjacent, normally perfused myocardium in conscious dogs 1-3 weeks after recovery from coronary artery occlusion. With coronary artery occlusion induced by a hydraulic occluder, endocardial blood flow ( Through a thoracotomy in the fifth left intercostal space, miniature pressure gauges (Konigsberg Instruments) were implanted in the left ventricle through a stab woun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

1983
1983
1993
1993

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…Of note, the magnitude of these changes in this conscious dog study were less than those found in their previous study in the anesthetized dog (Theroux et al, 1974). Velocity of nonischemic area segment shortening has been shown to increase at 5 and 15 minutes after coronary artery occlusion (Heyndrickx et al, 1975) but not after 1 hour (Cox and Vatner, 1982). Savage et al (1981) found a significant increase in wall thickening in the nonischemic area at 15 minutes, 1, 24, and 48 hours after coronary artery occlusion.…”
Section: Discussioncontrasting
confidence: 72%
“…Of note, the magnitude of these changes in this conscious dog study were less than those found in their previous study in the anesthetized dog (Theroux et al, 1974). Velocity of nonischemic area segment shortening has been shown to increase at 5 and 15 minutes after coronary artery occlusion (Heyndrickx et al, 1975) but not after 1 hour (Cox and Vatner, 1982). Savage et al (1981) found a significant increase in wall thickening in the nonischemic area at 15 minutes, 1, 24, and 48 hours after coronary artery occlusion.…”
Section: Discussioncontrasting
confidence: 72%
“…Heart rate increased from 82 ± 23 (mean + SD) to 123 ± 26 beats/min (p<.01) 10 min after circumflex coronary occlusion and remained elevated significantly 3 hr after occlusion. Left ventricular systolic pressure was not significantly changed but end-diastolic pressure increased from 13.4 + 4.8 to 18.6 ± 6.2(p<.01)and 18.1 + 6.8mmHg(p<.01) 10 Data are mean ± SD. C = control; TCO1 = early coronary occlusion (10 min); TCO2 late coronary occlusion (2.5 to 3.0 hr); HIR = heart rate (n = 14); LVSP = left ventricular systolic pressure (n = 14); LVEDP = left ventricular end-diastolic pressure (n = 1P); ( + )dP/dt = peak positive first derivative of left ventricular pressure (n = 13); ( -)dP/dt = peak negative first derivative of left ventricular pressure (n = 13).…”
Section: Resultsmentioning
confidence: 99%
“…Only those ischemic segments demonstrating homogeneous reductions of regional endocardial blood flow at both crystal sites were included in the final analysis. Heterogeneous ischemia was defined as a disparity in blood flow to the myocardium surrounding the two crystal sites ranging from 0.4 to 1.4 ml/min per g. This latter criterion was of critical importance, since segments with heterogeneous ischemia were previously shown to exhibit reductions of function similar to those with homogeneous reduction in regional endocardial blood flow (Cox and Vatner, 1982). Changes from control and differences among groups were analyzed by the method of two-way analysis of variance (Armitage, 1973).…”
Section: Methodsmentioning
confidence: 99%
“…Third, measurements of regional myocardial function were limited to the endocardium where homogeneous areas of ischemia could be monitored and confirmed by regional blood flow measurement. When the myocardium surrounding two ultrasonic crystals differed markedly in terms of level of flow reduction, these segments were excluded from the analysis, since these segments, although not uniformly ischemic, behave functionally as if they were homogeneously ischemic (Cox and Vatner, 1982). In the present investigation, 22 of 134 segments were excluded because of heterogeneous perfusion.…”
Section: Figure 7 Time Course Of Systolic Shortening In the Moderatementioning
confidence: 99%